2014
DOI: 10.1016/j.nbd.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that collaboration between HIF-1α and Notch-1 promotes neuronal cell death in ischemic stroke

Abstract: Recent findings suggest that Notch-1 signaling contributes to neuronal death in ischemic stroke, but the underlying mechanisms are unknown. Hypoxia inducible factor-1α (HIF-1α), a global regulator of cellular responses to hypoxia, can interact with Notch and modulate its signaling during hypoxic stress. Here we show that Notch signaling interacts with the HIF-1α pathway in the process of ischemic neuronal death. We found that a chemical inhibitor of the Notch-activating enzyme, γ-secretase, and a HIF-1α inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 49 publications
3
85
1
1
Order By: Relevance
“…Moreover, hypoxic preconditioning induces stroke tolerance in mice via HIF-1a signaling Wacker et al, 2012). Other studies, however, show that deletion or inhibition of HIF-1a resulted in reduced brain damage after ischemic stroke or hypoxic conditions, suggesting a detrimental role of HIF-1a (Helton et al, 2005;Chen et al, 2009a;Cheng et al, 2014).…”
mentioning
confidence: 99%
“…Moreover, hypoxic preconditioning induces stroke tolerance in mice via HIF-1a signaling Wacker et al, 2012). Other studies, however, show that deletion or inhibition of HIF-1a resulted in reduced brain damage after ischemic stroke or hypoxic conditions, suggesting a detrimental role of HIF-1a (Helton et al, 2005;Chen et al, 2009a;Cheng et al, 2014).…”
mentioning
confidence: 99%
“…Correlation analysis in this study could offer a strong evidence to reveal the influence of HIF-1α on hippocampal apoptosis in the rat model of epilepsy. It has been demonstrated that HIF-1a can accumulate enough to activate a pathway to apoptosis on the condition of hypoxia (Berger et al, 2013;Cheng et al, 2014). However, there is no evidence to support that HIF-1α is able to exercise influence on hippocampal apoptosis in the epileptic model.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that activity of γ-secretase and the resulting Notch1 activation, may endanger neurons in ischemic stroke by modulating pathways to increase vulnerability to apoptosis and by activating microglial cells and stimulating the infiltration of pro-inflammatory leukocytes Li et al 2012;Wang et al 2012). Furthermore it was shown in previous studies in this thesis and studies from other groups that Notch1 signaling endangers neurons after ischemic stroke by modulating nuclear factor-κB (NF-κB), pro-death protein Bim, hypoxia inducible factor-1α (HIF-1α) and caspase-3 Cheng et al 2014). …”
Section: Chapter 5 Notch1-jnk-c-jun Mediate Neuronal Cell Death Follomentioning
confidence: 87%
“…We have shown previously that γ-secretase activity and subsequent Notch signaling are elevated in the brain after ischemic stroke in vivo . Furthermore, γ-secretase activity was elevated in cultured primary neurons after ischemic conditions, and γ-secretase-mediated Notch signaling contributes to neuronal death in ischemic stroke by modulating the NF-κB, pro-death protein Bim, calcium signaling, HIF1α, and caspase pathways Cheng et al, 2014). Recent evidence indicates that Notch may mediate several of its physiological responses through MAPK pathways (Stockhausen et al, 2005;Kondoh et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation